Thermal progress of unsteady separated stagnation point flow with magnetic field and heat generation in hybrid ferroﬂuid - Najiyah Safwa, Khasi’ie; Waini, Iskandar; Nurul Amira, Zainal; Khairum, Hamzah; Abdul Rahman, Mohd Kasim; Norihan, Md Arifin; Pop, Ioan Mihai (MDPI, 2022)
This paper examines the unsteady separated stagnation point (USSP) flow and thermal progress of Fe3O4–CoFe2O4/H2O on a moving plate subject to the heat generation and MHD effects. The model of the flow includes the boundary layer and energy equations. These equations are then simplified with the aid of similarity variables. The numerical results are generated by the bvp4c function and then presented in graphs and tables. The magnetic and acceleration (strength of the stagnation point flow) parameters are the contributing factors in the augmentation of the skin friction and heat transfer coefficients. However, the enhancement of heat generation parameter up to 10% shows a reduction trend in the thermal rate distribution of Fe3O4–CoFe2O4/H2O. This finding reveals the effectiveness of heat absorption as compared to the heat generation in the thermal flow process. From the stability analysis, the first solution is the physical solution. The streamline for the first solution acts as a normal stagnation point flow, whereas the second solution splits into two regions, proving the occurrence of reverse flow.